Analisis Prediksi Kematian Pasien Covid-19 di Meksiko Menggunakan Algoritma Random Forest - Dennis Fitri Salsabilla Arianti; Latifah Arum Sulistyaningsih; Mohamad Burhanudin (INDONESIAN JOURNAL ON DATA SCIENCE, 2023)
This research aims to analyze and predict the deaths of Covid-19 patients in Mexico using the Random Forest algorithm. The data used in this study is sourced from official sources, including the number of cases, symptoms, risk factors, and Covid-19 patient mortality data. The first stage of this research is data preprocessing, where the acquired data is collected, cleaned, and prepared for analysis. Subsequently, data exploration is conducted to understand the characteristics and patterns within the dataset. Then, the Random Forest model is developed to predict the deaths of Covid-19 patients based on relevant factors. Model evaluation is performed using accuracy, precision, recall, and F1-score metrics. The results of this research indicate that the random forest model can provide good predictions for Covid-19 patient deaths in Mexico. The evaluation results show a high level of accuracy and satisfactory performance for the model. These findings can be used as guidance in decision-making and strategic planning to address the Covid-19 pandemic in Mexico. This research contributes significantly to the field of predictive analysis and provides valuable insights in the efforts to manage the Covid-19 pandemic.